2010
DOI: 10.1111/j.1600-0625.2010.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D‐binding protein polymorphisms are not associated with development of (multiple) basal cell carcinomas

Abstract: Vitamin D-binding protein (VDBP) single nucleotide polymorphisms (SNP) may affect skin carcinogenesis. The objective was to test the association between two functional VDBP SNPs and the susceptibility to (multiple) basal cell carcinomas (BCCs). Of the 7983 participants, 5790 (72.5%) and 5823 (72.9%) participants were genotyped for rs7041 and rs4588, respectively, and three haplotypes (Gc1s, Gc2 and Gc1f) were analysed. Two hundred and thirty-three persons developed a BCC of whom 122 (52.4%) developed multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…Association studies of DBP level have been performed to investigate their role in different types of cancer development, and obtained controversial results (Flohil et al, 2010;Mondul, Weinstein, Virtamo, & Albanes, 2012;Mondul, Weinstein, Moy, Mannisto, & Albanes, 2014;Wang, Eliassen, Spiegelman, Willett, & Hankinson, 2014;Weinstein et al, 2015). Mondul et al (2014) found that men with higher DBP concentrations were at significantly decreased risk of kidney cancer (OR ¼ 0.17, 95%CI: 0.08-0.33 for highest vs. lower quartile), a finding unchanged after adjustment for 25(OH)D.…”
Section: Dbpmentioning
confidence: 96%
See 1 more Smart Citation
“…Association studies of DBP level have been performed to investigate their role in different types of cancer development, and obtained controversial results (Flohil et al, 2010;Mondul, Weinstein, Virtamo, & Albanes, 2012;Mondul, Weinstein, Moy, Mannisto, & Albanes, 2014;Wang, Eliassen, Spiegelman, Willett, & Hankinson, 2014;Weinstein et al, 2015). Mondul et al (2014) found that men with higher DBP concentrations were at significantly decreased risk of kidney cancer (OR ¼ 0.17, 95%CI: 0.08-0.33 for highest vs. lower quartile), a finding unchanged after adjustment for 25(OH)D.…”
Section: Dbpmentioning
confidence: 96%
“…Moreover, a pooled analysis of published case-control studies did not show a significant association between GC rs2282679 and CRC (Hiraki et al, 2013). Furthermore, other studies including Colon Cancer Family Registry (Poynter et al, 2010), Cancer Prevention Study-II Nutrition Cohort (McCullough et al, 2007), Marie Study (Abbas et al, 2008), Nurses' Health Study , Rotterdam Study (Flohil et al, 2010), Shanghai Breast Cancer Study (Dorjgochoo et al, 2011), and Health Professionals Follow-up Study (Shui et al, 2012) did not show significant association between GC rs7041 and/or rs4588 and cancer at different sites as colon-rectum, pancreas, breast, endometrium, skin, and prostate. Otherwise, data from the Breast and Prostate Cancer Cohort Consortium provided evidence of a significant association between the rs2282679 variant and prostate cancer risk.…”
Section: Gc and Cancermentioning
confidence: 96%
“…Moreover, a pooled analysis of published case-control studies did not show a significant association between GC rs2282679 and colorectal cancer (41). Furthermore, other studies, including Colon Cancer Family Registry (42), Cancer Prevention Study-II Nutrition Cohort (43), Marie Study (44), Nurses' Health Study (19), Rotterdam Study (15), Shanghai Breast Cancer Study (45), and Health Professionals Follow-up Study (46), did not show significant association between GC rs7041 and/or rs4588 and cancer at different sites as colon-rectum, pancreas, breast, endometrium, skin and prostate. Otherwise, data from the Breast and Prostate Cancer Cohort Consorthium (47) provided evidence of a significant association between the rs2282679 variant and prostate cancer risk, which is not confirmed by the present meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Association studies of several polymorphisms in the GC gene and of DBP level have been performed to investigate their role in different types of cancer development and have obtained controversial results (15)(16)(17)(18)(19)(20)(21)(22)(23). Thus, we decided to carry out a comprehensive literature search and meta-analysis to investigate the association between different GC polymorphisms, DBP level and cancer risk, providing quantitative summary risk estimates of the association and identifying sources of between-study heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan çalışmalarda alel 2'nin makrofaj etkinleştirici özelliğinin daha az olduğu ve bunun sonucunda alel 2'yi taşıyan bireylerin makrofaj işlevinin daha düşük olduğu bildirilmiştir. Bugüne kadar yapıl-mış olan ve VDBP'yi kodlayan gendeki bu polimorfizmlerin (rs7041 ve rs4588) akciğer, [14] meme [15] ve prostat [16] kanseri ile ilişkili olduğunu öne süren çalışmalar olduğu gibi, GC polimorfizmlerinin prostat, [17] kolorektal kanser, [18,19] bazal hücreli karsinom [20] ve melanoma (sadece rs7041 incelenmiş) [21] ile ilişkisi olmadı-ğını bildiren çalışmalar da bulunmaktadır. Literatürde bugüne kadar VDBP polimorfizmi ile akciğer kanseri arasındaki ilişkiyi araştıran çalışma sayısı çok kısıtlı-dır.…”
Section: Bulgularunclassified